Application of Wireless Sensor in Automatic Device - Baolin, Su; Quanyu, Zhang; Boyang, Zhang (International Journal of Online and Biomedical Engineering (iJOE), 2018)
To improve the cost and accuracy in the positioning method of wireless sensor network in automatic devices, we proposed an improved distance based positioning method. We analyzed the positioning algorithm based on RSSI, TOA, TDOA, AOA distance measure. Due to different geographic shape, the right trajectory is important to the algorithm. We replaced hyperbola curve with asymptote in this study because the hyperbola positioning algorithm is not energy efficiency. We designed the positioning process of asymptote line algorithm. For the computational complexity, the hyperbola asymptotes are judged by the intersection point, which has an additional step compared to the maximum likelihood method. However, the maximum likelihood method must calculate the quadratic equations. The simulation results show that the algorithm proposed in this study is better than maximum likelihood method in positioning accuracy and the two algorithms have the same computational complexcity. The process of positioning presented in this study is simple and has a low cost.